IMPACT DESIGN ANALYSIS AND THE EFFECT OF PANDEMIC COVID-19 ON PERSONNEL READINESS IN MAINTAINING FORCE COMBAT ABILITIES - Harun Bekti Ariyoko; Ikhwan Syahtaria; Sukarno sukarno (Indonesian Naval Technology College STTAL, 2020)
ABSTRACT Personnel are one of the factors that shape operational readiness, in addition to platform and sewaco readiness. The outbreak of the Coronavirus Disease 2019 (COVID-19) virus, coupled with an increase in the number of cases that took place quite rapidly, and spread in a short time, has undeniably had a major impact, including on the military. In this study, the authors attempted to approach an impact analysis through a dynamic systems approach, to provide information that occurred as a result of the COVID-19 pandemic, through a pandemic impact analysis model. The results obtained are that combat capability does not automatically decrease due to the COVID-19 pandemic, because there are 4 factors that influence the value of combat capability. However, if personnel are negligent and indifferent to implementing the COVID-19 response protocol, coupled with the lack of a health support role and control function in personnel discipline in encouraging the handling and prevention of the COVID-19 pandemic, over time the value of combat capability will degrade. considering that the future conditions of war are increasingly unidentifiable or predictable due to uncertainty. Personnel readiness does not become the main reason for decreasing military combat capability, because personnel readiness is one of the four shaping factors in assessing combat capability. Keywords: COVID-19, Impact Analysis, Combat Capability, Personnel Readiness, System Dynamics